2022
DOI: 10.1186/s12906-022-03768-x
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of the ginger (Zingiber officinale) on Diabetic kidney disease, current knowledge and future direction: a systematic review of animal studies

Abstract: Objective Diabetic kidney disease affects approximately 40% of diabetic patients and is the leading cause of chronic kidney disease (CKD) worldwide. As a result, preventing renal complications in diabetic patients is critical. Ginger (Zingiber Officinale Rosco) is a popular spice and natral medicine. The present study was a systematic review focused on the existing evidence of the renoprotective effect of ginger extract on some features of diabetic kidney disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Various studies have shown that ginger can be an anti-inflammatory agent in treating type 2 diabetes mellitus [52,53]. Carvalho et al [54] found that the daily consumption of ginger in a 3-month human study reduced the level of triglycerides, fasting blood sugar, and LDL-cholesterol in patients with type 2 diabetes mellitus.…”
Section: Effect Of Mo and Ginger On Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Various studies have shown that ginger can be an anti-inflammatory agent in treating type 2 diabetes mellitus [52,53]. Carvalho et al [54] found that the daily consumption of ginger in a 3-month human study reduced the level of triglycerides, fasting blood sugar, and LDL-cholesterol in patients with type 2 diabetes mellitus.…”
Section: Effect Of Mo and Ginger On Type 2 Diabetes Mellitusmentioning
confidence: 99%